Epidemiological Assessment of Oral Cancer Burden in Pakistan. (26th November 2021) - Malkani, Naila; Kazmi, Sara; Rashid, Muhammad Usman
Abstract: Oral cancer ranks first among males and is the primary cause of cancer-related deaths in Pakistan. We studied the epidemiology and risk factors associated with this cancer. The main risk factors in the Pakistani population include the usage of chewable and non-chewable tobacco, areca nut, betel leaf, poor dental hygiene practices, oncogenic viral infections, and genetic predispositions. The impact of socioeconomic status and the available health resources on the management of oral cancer is also discussed. It is concluded that being a low-middle economy efforts should be primarily focused on awareness for early screening, diagnosis, and prevention strategies.